The burden of dialysis-requiring acute kidney injury among hospitalized adults with HIV infection: a nationwide inpatient sample analysis. (1st June 2015) - Nadkarni, Girish N.; Patel, Achint A.; Yacoub, Rabi; Benjo, Alexandre M.; Konstantinidis, Ioannis; Annapureddy, Narender; Agarwal, Shiv Kumar; Simoes, Priya K.; Kamat, Sunil; Menon, Madhav C.; Wyatt, Christina M.
Abstract : Objective: The objective of this study was to describe the incidence of acute kidney injury (AKI) requiring renal replacement therapy ('dialysis-requiring AKI') and the impact on in-hospital mortality among hospitalized adults with HIV infection. Design: A longitudinal analysis of a nationally representative administrative database. Methods: We reviewed the Healthcare Cost and Utilization Project's Nationwide Inpatient Sample Database, a large, nationally representative sample of inpatient hospital admissions, to identify all adult hospitalizations with an associated diagnosis of HIV infection from 2002 to 2010. We analysed temporal trends in the incidence of dialysis-requiring AKI and the associated odds of in-hospital mortality. We also explored potential reasons behind temporal changes. Results: Among 183 0041 hospitalizations with an associated diagnosis of HIV infection, the proportion complicated by dialysis-requiring AKI increased from 0.7% in 2002 to 1.35% in 2010. This temporal rise was completely explained by changes in demographics and an increase in concurrent comorbidities and procedure utilization. The adjusted odds of in-hospital mortality associated with dialysis-requiring AKI also increased over the study period, from 1.45 [95% confidence interval (95% CI) 0.97–2.12] in 2002 to 2.64 (95% CI 2.04–3.42) in 2010. Conclusion: These data suggest that the incidence of dialysis-requiring AKI among hospitalized adults with HIV infection continues to increase, and that severe AKI remains a significant predictor of in-hospital mortality in this population. The increased incidence of dialysis-requiring AKI was largely explained by ageing of the HIV population and increasing prevalence of chronic non-AIDS comorbidities, suggesting that these trends will continue. Abstract : Supplemental Digital Content is available in the text